(untitled) (Research, Society and Development, 2020)
In this article a bibliometric analysis of spinel ferrite production was carried out, with the purpose of to expanding the knowledge management on the research area, also identify future perspectives turned to the application of such structures and light to dry research. The study was designed based on a statistical and qualitative analysis of Web of Science (WoS) database documents from 1995-2017, using as an additional tool the CiteSpace software, which allows the expansion of the domain of knowledge on the subject With the acquirement of a set of bibliographic records of relevant publications, with subsequent identification of interlinked research groups (clusters). The CiteSpace software provides a set of empirical parameters, among them the so-called Betweenness Centrality (BC), which describes the influence of a given article on the transfer of information between the set of publications under study. Through the results it was possible to identify significant growth in the number of publications and citations. The countries with the highest number of publications are India (946), China (483) and the United States (247), with the US having the largest centrality parameter (BC), which reflects its prominent role in transmitting, information about spinel type ferrite. When analyzing the de-composition of WoS categories in large groups or clusters, we observed the predominance of three areas according to the number of co-citations: magnetic properties, electromagnetic properties and effect had electrocatalysis properties, which reflects the main objectives of research on this topic. Among the main keywords, “cobalt ferrite” has the largest BC parameter, revealing greater interest of the scientific community in Cobalt ferrite. The results of the clusters were corroborated from the identification of the main applications of spinel type ferrite in the last two years, in which the performance of these materials was observed predominantly in effluent treatment, magnetic devices, sensors and medical applications.